KEEFEKTIVAN MODEL PROBLEM BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SDN 6 PANGGANG - Paramitha, Angelina; Khamdun, Khamdun; Ari Pratiwi, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to measure the improvement of student learning outcomes by using the Problem Based Learning model of Pancasila Education class IV SDN 6 Panggang using the Pre-Experiment method, One-Group Pretest-Posttest Design research design, this study involved 25 fourth grade students of SDN 6 Panggang. Data collection techniques used are interviews, observations, tests (pretest and posttest) and documentation. Data analysis techniques include content validity tests followed by prerequisite tests including normality tests using the Shapiro Wilk test method, because the sample is small After the data is obtained, the hypothesis is tested, namely the N-Gain test. The results showed that the average pretest and posttest of learning outcomes increased from 66 to 82. With the results of the N-Gain test for learning outcomes obtained N-Gain, the average obtained is 0.4847. This shows that Ha is accepted and H0 is rejected, which means there is a significant difference in the application of the Problem Based Learning model to student learning outcomes in Pancasila Education subjects.